Modelling the upper airways of mandibular advancement surgery: A systematic review - Nik Ghazali, Nik Nazri; Abdul Latif, Mohd Faruq; Mohd Faizal, Abdullah; Ibrahim, Norliza; Mohd Razi, Roziana; Badruddin, Irfan Anjum (MDPI AG, 2023)
Obstructive sleep apnea syndrome is a conceivably hazardous ailment. Most end up with non-reversible surgical techniques, such as the maxillomandibular advancement (MMA) procedure. MMA is an amazingly obtrusive treatment, regularly connected to complexities and facial change. Computational fluid dynamic (CFD) is broadly utilized as an instrument to comprehend the stream system inside the human upper airways (UA) completely. There are logical inconsistencies among the investigations into the utilizations of CFD for OSAS study. Thus, to adequately understand the requirement for OSAS CFD investigation, a systematic literature search was performed. This review features the necessary recommendations to accurately model the UA to fill in as an ideal predictive methodology before mandibular advancement surgery.